Pharmacokinetics, tissue distribution, and antitumor activity of a novel compound, NY-2, in non-small cell lung cancer - Yingshi Zhang; Yingshi Zhang; Chang Xu; Chang Xu; Xiangbo Xu; Xiangbo Xu; Lingxiang Ma; Lingxiang Ma; Ruolan Li; Zihua Xu; Zihua Xu; Qingchun Zhao; et al. (Frontiers Media S.A., 2023)
Introduction: ZLDI-8, which has a relatively strong antitumor activity, is an inhibitor of ADAM-17 and acts on the Notch signaling pathway. To further optimize its structure and improve its activity, a series of derivatives of ZLDI-8 was synthesized. NY-2 was the most effective derivative based on preliminary activity screening in vitro, with no obvious toxicity after administration in vivo.Method: The study aimed to determine the pharmacokinetics, tissue distribution, hepatotoxicity, nephrotoxicity, and antitumor activity of compound NY-2 on non-small cell lung cancer (NSCLC) in vitro and in vivo.Results: The in vivo pharmacokinetics parameters of NY-2 were better than those of ZLDI-8. The tissue distribution analysis showed that tail vein injection of 6 mg/kg of NY-2 in rats resulted in the highest concentration in the lung, so we hypothesized that NY-2 might be effective in the treatment of non-small cell lung cancer. In vitro assays showed that NY-2 significantly inhibited tumor colony formation, invasion, and migration and increased LDH activity and apoptosis in a concentration-dependent manner in non-small cell lung cancer cells. NY-2 also inhibited the formation of lung metastases without significant toxicity to major organs in nude mice.Conclusion: Compared with the parent compound, ZLDI-8, the activity and safety of NY-2 were higher. NY-2 acts on ADAM17 and simultaneously affects the downstream Notch1 and integrinβ1 signaling pathways resulting in antitumor activity. Thus, NY-2 could be a potential antitumor agent, inhibiting the organization and development of non-small cell lung cancer.